A Case of Stress Cardiomyopathy With Nab-Paclitaxel Infusion - Harjinder Singh MD; Omair Ahmed MD; Erin Allen ACS; Hussein Othman MD (Journal of Investigative Medicine High Impact Case Reports, 2023)
Stress cardiomyopathy is a transient left ventricular dysfunction caused by physiologic or pathologic stressors. Anaphylaxis is a hypersensitivity disorder that can lead to a rapid life-threatening respiratory collapse. It happens due to exposure to allergens including medications. During anaphylaxis, there is a compensatory release of catecholamines that can lead to stress cardiomyopathy. In this case, nab-paclitaxel infusion led to anaphylaxis with respiratory failure. Echocardiogram showed features of diffuse hypokinesis with preserved basal segment contractility, and cardiac catheterization did not show any evidence of obstructive coronary artery disease. The overall clinical picture suggested stress cardiomyopathy. The patient was treated with guideline-directed medical therapy which resulted in normalization of the ejection fraction with no symptoms of congestive heart failure at any point. The patient was thereafter resumed on a reduced dose of nab-paclitaxel. This case report adds to the spectrum of infusion-related reactions associated with paclitaxel and demonstrates the course of events in the management of anaphylaxis and stress cardiomyopathy in this scenario.